2021
DOI: 10.1785/0220200261
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Noise Level in Eastern North China from ChinArray and Its Response to COVID-19

Abstract: High-frequency (>1  Hz) ambient noise is usually closely related to anthropogenic activities. During the outbreak and spread of the COVID-19, as various anthropogenic activities are restricted, high-frequency ambient noise level has been observed to be reduced on a worldwide scale. The continuous waveform data at dense broadband seismic stations from ChinArray in eastern North China provides a good opportunity to study the temporal and spatial patterns of the ambient noise level in the region, and to fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…These intricate signals are generally stronger during the day than at night, less intense on weekends than on weekdays, and more pronounced in urban areas than in rural areas [13,61,62]. Moreover, human activities can be influenced by inclement weather or traditional festivals [64,68,69]. As mentioned previously, the dominant frequency of cultural seismic noise ranges from 2 to 20 Hz in the GBA.…”
Section: Daily Human Activitymentioning
confidence: 84%
See 2 more Smart Citations
“…These intricate signals are generally stronger during the day than at night, less intense on weekends than on weekdays, and more pronounced in urban areas than in rural areas [13,61,62]. Moreover, human activities can be influenced by inclement weather or traditional festivals [64,68,69]. As mentioned previously, the dominant frequency of cultural seismic noise ranges from 2 to 20 Hz in the GBA.…”
Section: Daily Human Activitymentioning
confidence: 84%
“…Previous studies have shown that cultural seismic noise levels are closely related to regional population density and economic development [44,63,64]. Consequently, we analyzed the correlation between cultural seismic noise and population density [65] as well as gross domestic product (GDP) [66,67] in the GBA (Figures 5 and 6).…”
Section: Spatial Distribution Of Cultural Seismic Noise In the Gbamentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of 2019, novel coronavirus cases were diagnosed in Wuhan, China, and the virus was named COVID‐19 in February 2020 by the World Health Organization (Zhou et al., 2020). As the COVID‐19 epidemic escalated, different regions in China successively imposed epidemic control measures, such as restrictions on rallies, suspension of industrial production, management of floating populations, and health quarantine (W. Wang et al., 2021). On 23 January, China raised national public health response to the highest state of emergency‐ Level 1 of 4 levels of severity in the Chinese Emergency System (Tian et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the data set was large enough to challenge researchers to employ considerable computational resources to devise and perform novel large‐scale data‐hungry analyses, some of which have derived from the exploration seismology community (Burdick et al., 2014; Lin et al., 2011; Long et al., 2014). The success of well‐behaved data sets like USArray to drive innovation is evident in like‐spirited deployments that have followed it: IberArray in the Iberian Peninsula (Díaz et al., 2008), AlpArray in the Alps (Hetényi et al., 2018), and ChinArray in China (K. Wang et al., 2020; W. Wang et al., 2021; Zeng et al., 2020). Through these efforts and others, the continued growth of data volumes, computing availability, and the appetites of our algorithms is expanding the scope of seismic inquiry into emerging areas.…”
Section: Drivers Of Big Data Seismologymentioning
confidence: 99%